A FORMAÇÃO DOS TRABALHADORES NO BRASIL: NOTAS SOBRE O PERÍODO DA DITADURA E DA TRANSIÇÃO DEMOCRÁTICA - Salles Ramos, Moacyr; Stampa, Inez; dos Santos Santoro, Ana Cecília (LINKSCIENCEPLACE, 2026)
The article analyzes the professional education policy in two distinct periods: the military dictatorship and the democratic period. To do this choose the Pipmo, professional education program of the dictatorial period, and Pronatec, contemporary program. We conducted a literature review on the Pipmo, and bring data from a survey on the Pronatec completed in 2014. It was found that, despite the process of democratic transition, training for the work of the larger share of the working class still develops along the lines of period dictatorial, which is evidenced by the fact that the two programs in question present more similarities than differences mainly in the unequal socialization of knowledge.